The Borders and Lobato: An Exercise in Ethics (Interdisciplinary Studies Journal, 2021)
• This text, the result of reflections from the course "Frontiers of Thought," in the Stricto Sensu Postgraduate Master's Program in Education at the Faculty of Education of the State University of Minas Gerais, seeks to establish a dialogue between Education and considerations from various authors across many fields of knowledge. This dialogue is mediated by teachings found in The Yellow Woodpecker Ranch, a masterpiece by Monteiro Lobato. Thus, the Ranch itself, along with Dona Benta, Tia Nastácia, Tio Barnabé, Narizinho, Emília, Pedrinho, Visconde de Sabugosa, Cuca, and Saci Pererê, comes into play to foster discussions about power relations, democracy, decoloniality, equality of rights, respect, the need for change toward a better world, rationality and shame, the science of humanity, and the concepts of good and evil within teacher education. Finally, Ethics is also invited to this colloquium, aiming to open up possibilities for teaching better behaviors, enabling children, adolescents, and adults to live better on Planet Earth, grounded in fraternity, solidarity, and mutual respect.
Keywords: Frontiers of Thought; Education; Monteiro Lobato; The Yellow Woodpecker Ranch; Ethics